Evil and Christian Ethics. - Graham, Gordon, 1949 July 15- (New studies in Christian ethics., 2003)
This book interconnects contemporary moral philosophy with recent work in New Testament scholarship and makes a powerful case for the rejection of humanism and naturalism, explaining the moral obligation to struggle against evil by reference to the New Testament's cosmic narrative.